2′-5′-Oligoadenylate synthetase-like protein inhibits intracellular M. tuberculosis replication and promotes proinflammatory cytokine secretion. (February 2020) - Leisching, G.; Ali, A.; Cole, V.; Baker, B.
Highlights: OASL is expression is related to pathogenicity and virulence of mycobacteria. Intracellular mycobacterial replication increases following OASL knock-down. OASL enhance TNFα, IL-1β and MCP-1 secretion during M. tb infection. OASL plays a role in host defence mechanisms during pathogenic mycobacterial infection. Abstract: Host cytoplasmic surveillance pathways are known to elicit type I interferon (IFN) responses which are crucial to antimicrobial defense mechanisms. Oligoadenylate synthetase-like (OASL) protein has been extensively characterized as a part of the anti-viral mechanism, however a number of transcriptomic studies reveal its upregulation in response to infection with a wide variety of intracellular bacterial pathogens. To date, there is no evidence documenting the role (if any) of OASL during mycobacterium tuberculosis infection. Using two pathogenic strains differing in virulence only, as well as the non-pathogenic M. bovis BCG strain, we observed that pathogenicity and virulence strongly induced OASL expression after 24 h of infection. Further, we observed that OASL knock down led to a significant increase in M. tb CFU counts 96 h post-infection in comparison to the respective controls. Luminex revealed that OASL silencing significantly decreased IL-1β, TNF-α and MCP-1 secretion in THP-1 cells and had no effect on IL-10 secretion. We therefore postulate that OASL regulates pro-inflammatory mediators such as cytokines and chemokines which suppress intracellular mycobacterial growth and survival.